Recent advances on bacterial quorum quenching as an effective strategy to control biofouling in membrane bioreactors. (September 2021) - Syafiuddin, Achmad; Boopathy, Raj; Mehmood, Muhammad Aamer
Abstract: Physicochemical technologies to control biofouling in the membrane bioreactors (MBRs) have shown to be incapable of removing all biofouling layers. Novel biological approaches are needed to control biofouling. This paper aims to comprehensively review the recent advances in bacterial quorum quenching as an effective anti-biofouling strategy in the MBRs. The use of single bacterial species or a consortium has been proposed for the development of quorum quenching (QQ) strategies and has shown promising capability to degrade numerous acyl homoserine lactones (AHLs) and can delay the membrane fouling. Several strategies have been proposed to improve the durability of QQ by using various media including alginate and polyvinyl alcohol and to maintain the activities of functional microorganisms by using QQ strategy based on biostimulation. Although bacterial QQ can inhibit Gram-negative bacteria that are responsible for biofilm development, several studies also reported the enrichment of Gram-positive bacteria after applying QQ in MBRs. Graphical abstract: Unlabelled Image Highlights: Bacterial QQ for biofouling control in membrane bioreactors are reviewed. The use of single bacterial species or consortium has been tested for QQ technology. Bacterial QQ can delay the membrane biofouling in membrane bioreactors. Future QQ technology must consider not only for AHLs but also for AIPs, and AI-2.